Social Mechanisms in Empirical Sociology: Introduction to Special Issue. (September 2016) - Edling, Christofer; Rydgren, Jens
The social mechanism program has been successful in sociology and neighboring social science disciplines, such as criminology and political science. However, in our view the literature on social mechanisms is still too preoccupied with intratheoretical and metatheoretical discussions, and we find very few empirical applications. This is surprising since one of the basic aims of the social mechanisms approach from the start has been to achieve better integration between theory and empirical analyses. Yet of all the previous edited volumes and special issues dedicated to social mechanisms (or to analytical sociology, for that matter), we find only a small number of chapters that are empirically oriented in the sense that they address and try to answer a substantive empirical research question. This is unfortunate: By leaving out the dirty work of empirical analysis, social mechanisms theorists risk surrendering the potential influence of the approach. As a result, new (statistical) methods rather than new approaches to theorizing drive the practice of social science research. Most social scientists are driven by substantial empirical interests, that is, they share a set of questions they want to find answers to, rather than being motivated by abstract methodological and/or theoretical interests. Proponents of the social mechanism approach need to show by example that this approach is a valuable framework for researching broad, mainstream social science issues. This is what we do in this special issue.